English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

The formula for the distance is:
sqrt((x2-x1)^2+(y2-y1)^2)
sqrt((4-2)^2+(2-7)^2)
sqrt(2^2+(-5)^2)
sqrt(4+25)
sqrt(29)
~ 5.385

2007-01-26 12:18:11 · answer #1 · answered by Mark P 5 · 0 0

(4,2) and (2,7)

D = sqrt((2 - 4)^2 + (7 - 2)^2)
D = sqrt((-2)^2 + 5^2)
D = sqrt(4 + 25)
D = sqrt(29)

ANS : about 5.3852

2007-01-26 14:47:18 · answer #2 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers